Evaluation of radiation-induced Class V dental caries in patients with head and neck cancers undergoing radiotherapy - Siavash Savadi Oskoee; Parnian Alizadeh Oskoee; Farshad Seyednejad; Narmin Mohammadi; Mohammad Esmaeil Ebrahimi Chaharom (Tabriz University of Medical Sciences, 2008)
Background and aims. Salivary glands are very susceptible to radiation and any disturbances in their function are detrimental to the hard tissues in the oral cavity. The aim of this study was to evaluate posterior class V dental caries in patients with head and neck cancers undergoing radiotherapy. Materials and methods. In this study, twenty seven patients undergoing conventional radiotherapy were included. Class V dental caries of posterior teeth in these patients were evaluated in three intervals: before treatment, 3 weeks after the initiation of the treatment, and at the end of the treatment. Differences of mean caries activity between intervals were evaluated using paired sample t-test. Results. There were no class V decays prior to radiotherapy. Mean percentage of class V caries three weeks after radiotherapy and at the end of radiotherapy were 28.42% ± 14.41 and 67.05% ± 19.02, respectively. There were statistically significant differences in mean values among three stages (P = 0.00025). Conclusion. The results of the present study revealed that radiotherapy in patients with head and neck cancers causes class V dental caries on posterior teeth.